Efektivitas Kombinasi Sari Kurma dengan Jeruk Lemon dan Jeruk Nipis Terhadap Kadar Hemoglobin Mahasiswa Kebidanan Poltekkes Kemenkes Jambi - Herawati, Netti; Nurmisih, Nurmisih; Hairunnisya, Hairunnisya (NHM PRESS, 2025)
Anemia remains a public health concern, especially among adolescents and women of reproductive age. Midwifery students are a high-risk group due to intense academic demands and irregular eating habits. Natural-based interventions such as date extract and citrus fruits may help improve hemoglobin levels. The aimeds to determine the effectiveness of date extract combined with lemon and lime in increasing hemoglobin levels among midwifery students at Poltekkes Kemenkes Jambi.This study used a quasi-experimental design with a two-group pretest-posttest approach. A total of 40 students were divided into two groups: date-lemon and date-lime combinations. The intervention lasted for 7 days, and hemoglobin levels were measured before and after using a digital Hb set (Easy Touch). Data analysis used Wilcoxon and Mann-Whitney tests with a significance level of 5%. Both groups showed significant increases in hemoglobin levels after the intervention. The increase in the date-lemon group (from 11.505 to 12.890 g/dL) was higher than in the date-lime group (from 11.425 to 12.145 g/dL). Statistical analysis revealed p-values < 0.05 for both groups, indicating a significant effect, with the lemon combination being more effective. Both date-lemon and date-lime combinations effectively increased hemoglobin levels, but the combination with lemon showed greater effectiveness. This natural intervention may serve as an alternative approach to managing mild anemia among young adults